LSD1 induces H3 K9 demethylation to promote adipogenesis in thyroid-associated ophthalmopathy - Yuyan Xu; Jing Hu; Yuhang Fan; Licheng Sun; Ning Shen; Qihuang Jin; Ling Zhang; Jin Zhang; Fang Zhang; Hui Chen (Epigenetics & Chromatin)
Abstract Background Thyroid-associated ophthalmopathy (TAO) is an autoimmune orbital disease influenced by multiple factors, including genetic and immune factors. The enlargement of orbital fat tissues are mainly due to abnormal activation of adipocyte differentiation. Epigenetic modifications provide mechanistic insight for regulating gene expression and cellular differentiation. Lysine specific demethylase 1 (LSD1) is reported in regulation of adipogenesis. Therefore, it is critical to investigate the relationship between epigenetic modifier LSD1 and histone modification level during TAO process. Results In this study, combined with the clinic study and highthrough sequencing approach, our results revealed that the volume of orbital fat tissue was lower in TAO patients compared to non-TAO patients, whereas the number of adipocytes was higher in TAO patients compared to non-TAO patients, the expression level of adipocyte differentiation markers were higher in TAO samples. Consistently, at the cellular system, the expression level of adipogenic markers were higher in the TAO derived cells compared with the non-TAO cells. And we found LSD1 was highly expressed in TAO-derived cells. However, knocking down LSD1 decreased the expression of adipocyte markers. Mechanistically, LSD1 promoted adipocyte gene activation by demethylating H3K9me2 at the promoter regions. Finally, treatment with pargyline, an LSD1 inhibitor, inhibited adipogenesis in a dose-dependent manner, and the same inhibition of adipogenesis results were obtained with treatment with teprotumumab alone or combined with pargyline. Conclusions Overall, our study indicates that epigenetic modifications were dysregulated in TAO process, and these data elucidated a novel mechanism of adipocyte differentiation during TAO progression and positioned LSD1 as a potential anti-adipogenesis target in TAO. Further understanding of the interaction betwen transcription factors and epigeneic modifiers or other histone modifications in TAO is essential for providing new perspectives in TAO mechanistic study and clinical intervention. Graphical Abstract